Preface - Elżanowski, M.; Epstein, M.; Kotowski, R. (Archives of Mechanics, 1998)
This volume of the Archives of Mechanics contains papers presented at the Fourth Meeting on Current Ideas in Mechanics and Related Fields held in Kraków, at the Collegiuin Maius of the Jagiellonian University, from August 25-th through 28-th, 1997. Following in format and in spirit the previous three meetings (Portland - 1991, Banff -1993 and Segovia - 1995) this symposium was of a special character, as its main feature was the celebration of the 70-th birthday of Professor HENRYK ZORSKI.